Engineering Design and Rapid Prototyping - Kamrani, Ali K.; Nasr, Emad Abouel; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
"Engineering Design and Rapid Prototyping" offers insight into the methods and techniques that allow for easily implementing engineering designs by incorporating advanced methodologies and technologies. This book contains advanced topics such as feature-based design and process planning, modularity and rapid manufacturing, along with a collection of the latest methods and technologies currently being utilized in the field. The volume also: -Provides systematic design and solution methodologies for both design and manufacturing -Discusses product life cycle development and analysis for ease of manufacture and assembly -Offers applied methods and technologies in rapid prototyping and manufacturing "Engineering Design and Rapid Prototyping" will be extremely valuable for any engineers and researchers and students working in engineering design.
Product Development and Managements -- Engineering Design and Innovations -- Product Development Process -- Modular Design -- Design for Modularity -- DFMo Case Study: Four-Gear Speed Reducer Design -- Design for Manufacture and Assembly -- CAD/CAM and Features-Based Technologies -- Computer-Based Design and Manufacturing -- Feature Representations -- Feature Extraction Techniques -- Rapid Design and Manufacturing -- Engineering Materials: An Overview -- Geometric Dimensioning and Tolerancing -- Rapid Prototyping -- Data Mining Methodology and Techniques -- Group Technology and Applications.
Keywords: Engineering; Engineering design; Industrial engineering; Machinery; Engineering; Engineering Design; Manufacturing, Machines, Tools; Industrial and Production Engineering